How God copes with our faults: Bonhoeffer's exciting faith in God's action in history - In a discussion with "open theism" Wie Gott fertig wird mit unseren Fehlern: Bonhoeffers spannungsvoller Glaube an Gottes Handeln in der Geschichte - Im Gespräch mit dem «open Theism» - Teuchert, Lisanne (Evangelische Theologie, 2016)
The essay deals with a central question of the doctrine of providence under the conditions of modernity drawing on Bonhoeffer. How can we conceptualize God's action in a «world come of age»? Starting from the unresolved tension between God's omnipotence and powerlessness in Bonhoeffer's oeuvre, this contribution traces this question on the basis of the «articles of faith on the sovereignty of God in history» (in: Prisoner of God: Letters and Papers from Prison, enl. ed. 1997), drawing parallels from here to open theism, a recent development of US-American theology that reformulates God's omnipotence into omni-competence: God copes with our decisions and actions. The problems resulting from this theorem are solved with the help of another category of Bonhoeffer's, namely of a claim. God's action hence appears as claiming a world come of age.
CRIS-Team Scopus Importer:2024-09-30